Methods of quantitative limitation are in Ukraine - Щербатюк, Наталія Володимирівна; Чичирко, Сергій Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
Legal frameworks of instruments of the untariff adjusting of foreign economic activity are certain in thearticle. The division of untariff limitations is analysed. An author is undertake a detailed study of licensingand quota in Ukraine on the modern stage of development of external economic connections.